2022
DOI: 10.1002/jssc.202200457
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and network pharmacological analysis to explore the mechanism of ginseng treatment for spleen‐qi deficiency

Abstract: Ginseng is the main Chinese herbal medicine for tonifying Qi and invigorating the spleen. It has been used to treat spleen‐qi deficiency with good protective effects for thousands of years, however, its biological mechanism has not been fully elucidated. This study aims to explore the mechanism of ginseng in the treatment of spleen‐qi deficiency by using a comprehensive method combining metabolomics and network pharmacological analysis. Gas chromatography‐mass spectroscopy was applied for investigating the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…IL2 is necessary for T cell proliferation and other immune regulation [25]. EGFR and PTGS2 regulate multiple anti-inflammatory and immunomodulatory signaling pathways [45]. GO and KEGG enrichment analysis showed that the signaling pathways were mainly enriched in viral infection, bacterial infection, inflammatory pathway, immune pathway, and cancer, which may be related to the anti-inflammatory pathway of immune cells where TNF is located.…”
Section: Discussionmentioning
confidence: 99%
“…IL2 is necessary for T cell proliferation and other immune regulation [25]. EGFR and PTGS2 regulate multiple anti-inflammatory and immunomodulatory signaling pathways [45]. GO and KEGG enrichment analysis showed that the signaling pathways were mainly enriched in viral infection, bacterial infection, inflammatory pathway, immune pathway, and cancer, which may be related to the anti-inflammatory pathway of immune cells where TNF is located.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. [8, 9] used GC‐MS to study the blood and urine of SQD rats and confirmed that the therapeutic effects of ginseng could be achieved by modulating multiple metabolic pathways. Therefore, ginseng and its active ingredients can improve the intestinal environment, regulate the structure of the flora, and improve metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography–mass spectrometry (GC/MS) metabolomics was adopted to study the metabolic profile changes in the urine of rats with spleen‐qi deficiency after ginseng treatment. Potential biomarkers were found to have participated in glycerolipid, taurine and hypotaurine, and β‐alanine metabolic pathways 20 …”
Section: Introductionmentioning
confidence: 99%
“…Potential biomarkers were found to have participated in glycerolipid, taurine and hypotaurine, and β-alanine metabolic pathways. 20 In the study reported here, we sequenced the microbial DNA extracted from the feces of experimental animals by 16s rRNA highthroughput sequencing technology (Illumina platform). The changes of SCFAs in intestinal contents were detected by GC/MS techniques.…”
mentioning
confidence: 99%